2010
DOI: 10.1002/hipo.20850
|View full text |Cite
|
Sign up to set email alerts
|

P2X7 receptor differentially modulates astroglial apoptosis and clasmatodendrosis in the rat brain following status epilepticus

Abstract: Recently, it has been reported that astroglial loss/dysfunction plays a role in epileptogenesis. In addition, astroglial loss is accompanied by up-regulation of P2X7 receptor expression in microglia. Therefore, we investigated whether P2X7 receptor is involved in astroglial damages induced by status epilepticus (SE). In the present study, astroglial loss showed the regional-specific manner and the differential responses to P2X7 receptor functions. Both OxATP and brilliant blue G (P2X7 receptor antagonists) inf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
49
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 53 publications
(58 citation statements)
references
References 69 publications
9
49
0
Order By: Relevance
“…These data corroborate other studies that also showed reduction in astrocytes loss in the molecular layer of the dentate gyrus and frontoparietal cortex following P2X7R antagonists oxidized ATP (OxATP) and BBG in pilocarpine model [40]. In contrast, some authors showed increased cell death in CA3 layer by using P2X7R antagonists OxATP, A-438079, and A-740003 following pilocarpine [39], and that inhibition of microglial activation by the P2X7R antagonists may not be sufficient to protect neurons of the excitotoxicity caused by SE [43].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…These data corroborate other studies that also showed reduction in astrocytes loss in the molecular layer of the dentate gyrus and frontoparietal cortex following P2X7R antagonists oxidized ATP (OxATP) and BBG in pilocarpine model [40]. In contrast, some authors showed increased cell death in CA3 layer by using P2X7R antagonists OxATP, A-438079, and A-740003 following pilocarpine [39], and that inhibition of microglial activation by the P2X7R antagonists may not be sufficient to protect neurons of the excitotoxicity caused by SE [43].…”
Section: Discussionsupporting
confidence: 92%
“…There are many studies aimed at elucidating the role of P2X7R in epilepsy using agonists and antagonists. The activation of P2X7R with Bz-ATP (P2X7R agonist) causes microglial activation, enhances TNF-α immunoreactivity, reduces astrocytes, and intensifies seizures expression [19,[38][39][40]. Conversely, P2X7R blockage promotes anticonvulsant effects and reduces electroencephalographic and behavioral seizures, IL-1β production, microglial activation, recruitment and infiltration of neutrophils into the frontoparietal cortex, and damage resulting from seizure [14,15,33,38,[41][42][43][44].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, Takenouchi et al (2009) reported that P2X7R activation negatively regulated autophagic flux through the impairment of lysosomal functions. Similarly, we have reported that P2X7R antagonists, such as BBG and OxATP, increased clasmatodendrosis (Kim et al 2010b). With respect to these previous reports, clasmatodendrosis may be one of autophagy-related degeneration of astrocytes following SE.…”
Section: Introductionsupporting
confidence: 67%
“…We have recently reported that SE results in caspase-3-independent/AIF-dependent apoptosis-like degeneration of astrocytes in the molecular layer of rat dentate gyrus (Kang et al 2006;Kim et al 2008Kim et al , 2010b. SE also induces astroglial death through severe vasogenic edema in the piriform cortex (Kim et al 2010c).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation